Crossing the ice: an Iron Age to medieval mountain pass at Lendbreen, Norway. (April 2020) - Pilø, Lars; Finstad, Espen; Barrett, James H.
Abstract: Abstract : Mountain passes have played a key role in past mobility, facilitating transhumance, intra-regional travel and long-distance exchange. Current global warming has revealed an example of such a pass at Lendbreen, Norway. Artefacts exposed by the melting ice indicate usage from c . AD 300–1500, with a peak in activity c . AD 1000 during the Viking Age—a time of increased mobility, political centralisation and growing trade and urbanisation in Northern Europe. Lendbreen provides new information concerning the socio-economic factors that influenced high-elevation travel, and increases our understanding of the role of mountain passes in inter- and intra-regional communication and exchange.